Polishing and lapping of silicon discs at Texas Instruments - Students of The College of Aeronautics (College of Aeronautics, 1965)
The polishing and lapping of silicon discs at Texas Instruments Ltd. was investigated by a team of students from Cranfield as a project for the Spring Term, January/March 1965. CAD Unfortunately, the process was not operating during the period available to the team and therefore detailed measurements could not be obtained. This report is based on discussions with Texas Instruments, on analysis of a short film of the main parts of the process and subsequent analyses and investigations. Although a detailed and quantitative list of precise recommendations cannot be made, a number of worthwhile points arise together with some suggestions for longer term investigation. The Cranfield team has learnt a great deal from the project, but there is naturally a sense of frustration at not being able to present a complete and comprehensive analysis of the process.